A Cross Sectional Study on Factors Associated with Disease Progression Among Breast Cancer Patients Treated with Endocrine Therapy - Rani, Nurul Sahida; Wahab, Mohd Shahezwan Abd; Zulkifly, Hanis Hanum; Mohamad, Siti Hartinie (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Endocrine therapy (ET) has shown clinical benefits for hormone receptor (HR)-positive breast cancer (BCa) patients. Following ET initiation, patients’ response to treatment is monitored by assessing disease progression (PD). The study aims to identify the factors associated with PD, 1 year after ET initiation in HR-positive BCa patients at Hospital Sultanah Nur Zahirah (HSNZ), a public hospital in Terengganu, Malaysia. Patients were identified from the Terengganu Cancer Registry. Female patients, aged ≥ 18 years old, diagnosed with HR-positive BCa during the period from 2011 - 2014, and prescribed with at least one type of ET were included and followed-up for 5 years. Electronic medical records were reviewed for socio-demographic and clinical data. PD that occurred after 1 year of ET initiation were recorded. Adherence was measured by calculating the medication possession ratio (MPR). MPR value of <0.8 indicated non-adherence to ET. Overall, 103 BCa patients were included in the study. After one year of ET initiation, 31.1% (32/103) of patients had PD. Mean MPR values (± SD) during the first, third and fifth year of ET were 0.70±0.26, 0.66±0.29 and 0.60±0.32, respectively. Late stage BCa (p=0.007), distant metastasis at diagnosis (p=0.002), MPR value of < 0.8 in the first year of treatment (p=0.003), high comorbidity and a history of complementary and alternative medicine (CAM) use (p=0.036) were associated with PD. Adherence to ET should be emphasized in BCa patients. Women should be encouraged not to delay treatment for BCa. Pharmacists and physicians should be vigilant about CAM use in BCa patients.